Reproductive biology of Sclerodermus brevicornis, a European parasitoid developing on three species of invasive longhorn beetles - Lupi, Daniela; Favaro, Riccardo; Jucker, Costanza; Azevedo, Celso O.; Hardy, Ian C.W.; Faccoli, Massimo (Elsevier, 2017)
The reproductive performance of Sclerodermus brevicornis (Kieffer), a bethylid wasp native to Europe, was evaluated on three species of facticious hosts. These are longhorn beetles which have recently invaded Europe from Asia: Anoplophora glabripennis (Motschulsky), Anoplophora chinensis (Forster) and Psacothea hilaris hilaris (Pascoe) (Coleoptera: Cerambycidae). Sclerodermus brevicornis attacked all three species, but offspring only developed to maturity on medium and large sized host larvae. Host species influenced the duration of parasitoid development and the number of offspring maturing, both were greatest on A. glabripennis, with up to 373 adult parasitoids emerging from a single host. The sex ratios of S. brevicornis broods were strongly female biased (ca. 9% males). We conclude that S. brevicornis has the potential to be efficiently mass-reared and actively deployed in the biological control of invasive longhorn beetles. Further progress should be encouraged by the successful use of other species of Sclerodermus against beetle pests in China.